Reduction of the embrittlement effect of binder contamination in MIM processing of Ti alloys. (27th May 2017) - Ebel, Thomas; Beißig, Tobias; Ebner, Sandra; Luo, Xia; Nagaram, Anok Babu; Zhao, Dapeng
ABSTRACT: During metal injection moulding (MIM) processing, titanium tends to react with carbon from the polymeric binder. Thus, carbides, which can effect embrittlement, might be formed if the carbon solubility of the alloy is exceeded. Especially in β-titanium alloys, this is a critical issue, because β -phase stabilising elements like V, Mo and Nb decrease the carbon solubility of the Ti-matrix. This study summarises studies with different approaches to limit carbide precipitation in a Ti–22wt-%Nb alloy processed by MIM. Adding Zr led to a significant reduction in the amount and size of carbides due to an increase in the lattice constant. Furthermore, boron was added supporting a finer distribution of the carbides. Scanning electron microscopy and transmission electron microscopy investigations reveal the role of the elemental additions and analyse the structure of the different carbides formed. Combinations with heat treatments led to significant reduction in the amount of carbides.